(untitled) (Research, Society and Development, 2020)
One Health is a rising concept that has emerged in order to clarify and transparently convey the coalition between human health, animal health and the ecosystem where they operate, focusing on the promotion of collective health in its cosmopolitan face. This study aimed to report the experience of working on the theme of Unique Health from the perspective of popular health education, contributing to the construction of knowledge about the interaction between human, animal and environmental health. This is a descriptive research with a qualitative approach, in the form of an experience report, on the performance of the Extension Project “University Promoting Health” at the Federal Rural University of Semi-Arid, along with public schools in underserved communities in Mossoró - RN and region, where the theme of Single Health was approached from the perspective of popular health education. 714 students from 14 public schools in the potiguar semiarid were worked through playful and participatory approaches, with pedagogical strategies aimed at promoting the autonomy of students. There was a strengthening of ties between the parties involved in the project, with engagement and significant satisfaction. The relationship established between the team and the students facilitated the dialogue between the parties, enabling the formation of subjects with knowledge and citizen awareness in the aspect of unique health. Finally, the search for new models of working with health in needy communities should be a constant initiative, with the aim of carrying out innovative collective activities and discussing relevant issues for the population.